Wildfowl of the Hemiarctic - Driver, P M (Wildfowl, 1959)
I spent 3 months in the summer of 1958 with my assistant, C. W. Nicol, in the Hemiarctic to the south of Ungava Bay. This lies between Hudson Bay and Labrador and carries a large population of Sea Ducks, of various sorts, scattered around the coasts and estuaries. As the Tree Line however reaches the southern end of Ungava Bay, one may also find species of ducks not characteristic of the Arctic, and I will attempt to give an impression of the wildfowl population of the region by referring to the birds seen by us. Where possible, I will give the local eskimo name for the species. It must be borne in mind that for much of the time we were restricted to the area of camp some 15 miles upstream from the Bay, but we did make occasional trips across the Tundra and up and down the river.